PARENTAL EXPECTATIONS AND PRIMARY EDUCATION CURRICULUM IN NEPAL - Shah, Rajendra Kumar (Sanata Dharma University Yogyakarta, 2020)
The major aim of the present study is to study the expectation of the parents regarding the primary education curriculum. Descriptive survey method has been adopted in the present study. Conducted through survey model, this study involves semi-structured interviews with 205 parents of the primary schools children of Ramaroshan Municipality-4, Achham, Province no. 7, Nepal. According to data were analyzed through descriptive analysis technique. Results of the present study indicate that parental expectations on the objectives of primary education are mostly in conformity with the general objectives of primary education. Accordingly, majority of them even suggested teaching moral behaviours, health habits, and other as subjects. Parents complaints there is lack ofÂ discipline in schools; low academic qualification of teachers; lack of dedication on the part of teachers; loose administration in the school; lack of supervision from the office concerned; teaching not usually done through the whole period and the school hours; ineffective teaching; too many holidays; no regular teaching in the school due to irregularity and negligence of teachers; and no emphasis on cultural and physical development of children. But a majority of the parents are unaware of interesting area of their children, interesting area of children, and reading subjecting of their children.DOI: 10.24071/ijiet.2020.040103